Resafa, Syrien. Die Arbeiten der Jahre 2017 bis 2019 - Konrad, Michaela; Sack, Dorothée; Fugger, Verena; Gussone, Martin (e-Forschungsberichte des DAI, 2020)
The work within the Resafa-project focusses on the scholarly analysis of the fieldwork that has been undertaken since the early years of the excavations in the 1950s. In two teams working at the University of Bamberg (M. Konrad, V. Fugger) and the University of Technology Berlin (D. Sack, M. Gussone) our research that is conducted in different interdisciplinary cooperations aims to a superordinate interpretation of the early Christian pilgrimage site within its multiple environmental, political, social, ethnic and religious networks in a diachronic perspective throughout the time of its existence. Parallel and as a material base to these studies the work on the detailed reconstruction of the development of the site between the 1st and the 13th century AD was continued. Furthermore the analysis of the city walls and the so-called “Zentralbau“ as well as research on the mainly Byzantine and Early Islamic structures in the extra mural areas completed our knowledge about the fine chronology of the site, its infrastructure and surroundings.